Purse-String Suture for Skin Closure Following Large Thyroidectomy - Kurnia, Ahmad; Siregar, Bintang Abadi; Ramli, Muchlis (UI Scholars Hub, 2020)
Introduction. The total number of patients with thyroid nodules, especially large thyroid nodules (> 6 cm diameter), is increasing. However, the conventional suturing technique for closure of thyroidectomies is still only recommended as the standard for the tumor with a diameter up to 6 cm. Hence, this study aims to prove another surgical technique, purse-string stitching technique, for better esthetic outcomes on large thyroidectomy. Methods. This study was a non-randomized control trial. The subjects included the patients of Cipto Mangunkusumo Hospital in 2013 to 2014 with a thyroid tumor > 6 cm in diameter without any history of anterior cervical surgery and positive lymph nodes. Subjects were divided into the purse-string group and the conventional group. Thyroidectomies were done on all subjects, then were closed by the suturing technique of each group. Outcomes were recorded in the follow-up sessions, including wound scar size, wrinkle existence, and subject’s satisfaction level. Results. Purse-string technique resulted in shorter scar length compared to the conventional technique (median 35 mm vs. 94 mm, p< 0.01). The other outcomes, such as the width of the scar (median 3 mm vs. 2 mm, p=0.265), the presence of wrinkles (0 vs. 2, p=0.480), and satisfaction level of subjects (median 9 vs. 9, p=0.287) were also assessed. Conclusion. The purse-string suturing technique on large thyroidectomy wound closure could be an alternative, besides the conventional suturing technique for a better esthetic result.